2017
DOI: 10.3389/fmicb.2017.00604
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pullorum: An Emerging Zoonotic Pathogen

Abstract: Helicobacter pullorum (H.pullorum) commonly colonizes the gastrointestinal tract of poultry causing gastroenteritis. The bacterium may be transmitted to humans through contaminated meat where it has been associated with colitis and hepatitis. Despite the high prevalence of H. pullorum observed in poultry, little is known about the mechanisms by which this bacterium establishes infection in host and its virulence determinants. In this article we aim to provide an overview of this emerging zoonotic pathogen; its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 56 publications
0
18
1
3
Order By: Relevance
“…Based on a recent review which discussed water as source of H pylori, it was concluded that even if confirmed as a reservoir for H pylori, water most likely would be only be a secondary route of transmission. 2 Our study did not show any 22 Other Helicobacter spp of animal origin such as Helicobacter canis (from dogs and cats), 23 Helicobacter pullorum (from poultry), 24 and Helicobacter suis (from pigs) 25 were found to cause infection in human.…”
Section: Re Sultscontrasting
confidence: 55%
See 1 more Smart Citation
“…Based on a recent review which discussed water as source of H pylori, it was concluded that even if confirmed as a reservoir for H pylori, water most likely would be only be a secondary route of transmission. 2 Our study did not show any 22 Other Helicobacter spp of animal origin such as Helicobacter canis (from dogs and cats), 23 Helicobacter pullorum (from poultry), 24 and Helicobacter suis (from pigs) 25 were found to cause infection in human.…”
Section: Re Sultscontrasting
confidence: 55%
“…On the other hand, higher seroprevalence was reported in children with sheep contact compared to children without sheep contact in Poland . Other Helicobacter spp of animal origin such as Helicobacter canis (from dogs and cats), Helicobacter pullorum (from poultry), and Helicobacter suis (from pigs) were found to cause infection in human.…”
Section: Discussionmentioning
confidence: 98%
“…The abundance of Coriobacteriaceae that can produce high levels of SCFAs resulting in competitive exclusion of unfavorable microorganisms [67] was enhanced by the majority of tested blends. In addition, tested blends reduced Helicobacteraceae abundance by reducing Helicobacter pullorum, which has been also isolated from cecal epithelial cells [68] and shown to have a pathological outcome in the gut of chickens [69].…”
Section: The Relevance Of Organic Acids and Essential Oils Combinatiomentioning
confidence: 99%
“…H. pullorum es una bacteria zoonótica que, al igual que algunas especies de Campylobacter, es un colonizador frecuente del tubo digestivo de las aves de corral y de otros animales 1,2 . En ciertas ocasiones, esta bacteria ha sido aislada en personas sanas 7 .…”
Section: Discusión Y Conclusionesunclassified
“…Sin embargo, la patogenicidad de las especies de este género va más allá, y pueden ocasionar patología tanto a nivel gastrointestinal (diarrea, enfermedad inflamatoria intestinal) como hepatobiliar. Helicobacter pullorum es una de estas especies capaces de ocasionar cuadros a estos niveles 1 . Coloniza el tracto gastrointestinal de los pollos y se cree que la forma de transmisión al ser humano es a través de carne contaminada 2 .…”
Section: Introductionunclassified